Resacralization of the sacred - Šter, Katarina (Muzikološki zbornik, 2014)
The Carthusians selected and emended the traditional liturgical chant texts of the liturgy in order to bring them closer to the biblical texts. The comparison of the selected responsories from various traditions (Carthusian, Benedictine, Cistercian, Cluniac, Aquitanian) shows that it was respect for tradition of the texts as well as the melodies that led the Carthusians in their successful re-sacralization of the repertoire.
Keywords: Biblija; cerkvena glasba; kartuzijanski koral; koralne tradicije; responzoriji